أهمية تطوير البنية التحتية السياحية في عملية الجذب السياحي - راجع ،نور الهدى إشراق; بوران ،سمية (جامعة الوادي University of Eloued, 2024)
تهدف هذه الدراسة إلى إبراز أهمية تطوير البنية التحتية للسياحة في عملية الجذب السياحي، ولتحقيق هذا الهدف تم إجراء دراسة تحليلية مقارنة لدول المغرب العربي الثلاث (الجزائر، المغرب، وتونس) خلال الفترة (2013-2023)، وذلك من خلال تحليل البيانات المجمعة من تقارير المنتدى الاقتصادي العالمي حول تنافسية السياحة والسفر، وبيانات البنك الدولي للسياحة الدولية. توصلت الدراسة إلى مجموعة من النتائج أهمها أن تطوير البنية التحتية للسياحة تعتبر العمود الفقري والعامل الأساسي في عملية جذب السياح وجذب الاستثمارات الأجنبية وتنمية قطاع السياحة، كما تم التوصل إلى أن الأداء السياحي لدول المغرب العربي ضعيف خاصة الجزائر سواء من حيث استقطاب السياح الوافدين أو من حيث مؤشرات البنية التحتية السياحية، وهذا لا يعكس فعلا المقومات السياحية وعناصر الجذب السياحي التي تتمتع بها هذه الدول. This studyaims to show the importance of developingtourism infrastructure in the process of touristattraction. To achieve thisa comparative analytical study was conducted for the three Arab Maghreb countries (Algeria, Morocco, and Tunisia), during the period (2013-2023),by analyzing the data collected from the reports of the world Economic forum on travel and tourism competitiveness, and the world Bank International Tourism Data. The study reached a set of results, the most important of which is that developing tourism infrastructure is considered the main factor in the process of attracting tourists, attracting investments and developing the tourism sector. It was also found that the tourism performance of the Maghreb countries is weak, especially Algeria, whether in terms of attracting incoming tourists or in terms of tourism infrastructure indicatos, and this does not actually reflect the tourism components and elements of tourist attraction that these countries enjoy.
The importance of developing tourism infrastructure in the process of tourist attraction -A comparative analytical study of the Arab Maghreb countries (Algeria, Morocco, Tunisia) during the period (2013-2023)
Keywords: البنية التحتية السياحية; الجذب السياحي; تنافسية السياحة; السياح; دول المغرب العربي; Tourism Infrastructure; Tourist attractions